Мodernization of Conventional Spiral Wound Channel - A Tool to Escape Fouling, Expand Membrane Life and Increase Recovery - Pervov, Alexei (Journal of Membrane and Separation Technology, 2014)
The survey shows that high operational costs of membrane facilities and large amounts of concentrate effluents are mainly attributed to fouling and scaling. The research of scaling and fouling mechanisms shows that these processes depend not only on hydrodynamic factors, but on membrane type and channel geometry. However, the main disadvantages of the modern RO techniques are connected with membrane fouling, concentrate flow, and complicated design. The main ways to develop new fouling-free techniques are outlined and suggest a new concept of modified "open-channel" spiral wound membranes. Successful attempts were undertaken by the author to modify spiral wound membrane channels to limit fouling and scaling potentials of membrane modules. Elimination of spacer mesh from the feed channels eliminates "dead" regions that provide scaling and fouling conditions whilst also reducing the risk of particle "trapping" and associated dramatic cross flow resistance increase. High recoveries could also be reached due to strong stability of calcium carbonate and sulphate solutions. Introduction of a new "open-channel" configuration offers new perspectives to escape fouling and develop a novel technique to treat water with high fouling and scaling potential. This novel concept of spiral wound module with an "open channel" design has been developed, field-tested and introduced into practice. A test procedure is described that enables us to compare fouling propensities of RO facilities tailored with different membrane types and channel configurations. Cross-flow resistance increase, scaling, and fouling rates and flux decrease are predicted for different feed water compositions. Introduction of new "open channel" spiral wound module into desalination practice enables us to considerately expand the application area of RO techniques.